Therapeutic Efficacy of Antioxidants in Ameliorating Obesity Phenotype and Associated Comorbidities - Tun, Steven; Spainhower, Caleb James; Cottrill, Cameron Lee; Lakhani, Hari Vishal; Pillai, Sneha S.; Dilip, Anum; Chaudhry, Hibba; Shapiro, Joseph I.; Sodhi, Komal (Frontiers in Pharmacology, 2020)
Obesity has been a worldwide epidemic for decades. Despite the abundant increase in knowledge regarding the etiology and pathogenesis of obesity, the prevalence continues to rise with estimates predicting considerably higher numbers by the year 2030. Obesity is characterized by an abnormal lipid accumulation, however, the physiological consequences of obesity are far more concerning. The development of the obesity phenotype constitutes dramatic alterations in adipocytes, along with several other cellular mechanisms which causes substantial increase in systemic oxidative stress mediated by reactive oxygen species (ROS). These alterations promote a chronic state of inflammation in the body caused by the redox imbalance. Together, the systemic oxidative stress and chronic inflammation plays a vital role in maintaining the obese state and exacerbating onset of cardiovascular complications, Type II diabetes mellitus, dyslipidemia, non-alcoholic steatohepatitis, and other conditions where obesity has been linked as a significant risk factor. Because of the apparent role of oxidative stress in the pathogenesis of obesity, there has been a growing interest in attenuating the pro-oxidant state in obesity. Hence, this review aims to highlight the therapeutic role of antioxidants, agents that negate pro-oxidant state of cells, in ameliorating obesity and associated comorbidities. More specifically, this review will explore how various antioxidants target unique and diverse pathways to exhibit an antioxidant defense mechanism.